Scientific Literacy Outcomes Following Discovery Learning with Simple Experiments: A Quasi-Experimental Study in Fourth-Grade Science - Syalaisyah Nabila Rahman; Marleny Leasa; Johanes Pelamonia; John Rafafy Batlolona (Journal of Pedagogy and Education Science, 2026)
Scientific literacy remains a major challenge in elementary science education because many students struggle to explain scientific phenomena, evaluate investigations, and interpret evidence. Although Discovery Learning and experimental activities have demonstrated positive outcomes, evidence regarding their integrated use in elementary schools, with scientific literacy as the primary outcome, remains limited. This study investigated the effect of Discovery Learning supported by simple experiments on fourth-grade students’ scientific literacy. A quantitative quasi-experimental pretest-posttest control-group design was employed. Participants were 68 fourth-grade students from SDN SPG Latihan Ambon, selected through simple random sampling and assigned to an experimental group (n = 35) and a control group (n = 33). Data were collected using a scientific literacy test developed from the PISA 2018 framework and analyzed using descriptive statistics and analysis of covariance (ANCOVA). The experimental group achieved a higher post-test mean score (82.80) than the control group (61.94). ANCOVA demonstrated a significant effect of the instructional model on scientific literacy (F = 237.390, p < 0.001), with a large effect size (partial eta squared = 0.785). These findings indicate that integrating Discovery Learning with simple experiments can strengthen scientific literacy by engaging students in active inquiry, evidence-based reasoning, and meaningful knowledge construction. The study provides empirical support for combining discovery-oriented instruction with experimentation in elementary science. Future studies should include larger and more diverse samples, investigate the durability of learning gains, and assess implementation across different science topics, grade levels, and educational settings.